A auxiliaridade do verbo “ir” na constituição do tempo : uma descrição centrada no uso - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This work has as goal to analyze the verbal auxiliary in constructions with the verb ir conjugated in the first and third person singular of the present indicative. To reach this verbal person, a search was carried out in the present and future tenses of the verb under study to identify the most frequent ones for analysis. In order to achieve the objective of this work, language studies were adopted from a theoretical perspective of usage based models, through mixed, quantitat ive and qualitative research. The data are on the language used by residents of the city of Goiás, extracted from 12 interviews from the Fala Goiana database, considering sex and age group. The research is based on the theoretical bases of Bybee (2010, 201 6), Croft (2001), Ferrari (2021), Fillmore (1982), Givon (2001), Goldberg (1995, 2006, 2013), Lakoff (1990), Lakoff; Jhonson (1980a e b), Langacker (2008), Lopes (2022), Martelotta (2023), Martelotta; Palomanes (2023), Neves, (2012, 2018, 2022), Silva (199 7) and Traugott; Trousdale (2021) for an approach to language from the theoretical perspective of usage based models, integrating contributions from Construction Grammar and cognitive functional linguistics. To deepen the studies on verbal auxiliary, in ad dition to some authors already mentioned above, we have as support Castilho (2014), Hopper (1982) and Ilari; Basso (2014). The research analyzed auxiliary periphrases of ir found in the database, being the formations ir + infinitive e ir + gerund. Through quantitative research, it was possible to identify that ir + infinitive is the most frequent formation among speakers and that the idea of movement is related to the two formations found in the data, but with distinct characteristics: ir + infinitive is ti me oriented and ir + gerund is aspectual oriented. In the analysis of the data, other constructions were also found that deviate from what is considered common, but which are functional, since they are all used for argumentation in interactive situations. Thus, it was possible to verify the variety of constructions with the verb ir as auxiliary, as well as its productivity due to the number of occurrences found in the database, proving that the use of these constructions is the result of the speaker's cogni tive capacity.
Keywords: Língua - uso; Auxiliaridade; Verbo ir; Language - usage; Auxiliary; Verb ir; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LETRAS::LINGUA PORTUGUESA